International Law for Diplomats - Oyarzabal, Mario JA (International Law E-books Online, Collection 2026., 2026)
The purpose of this book is to provide diplomats worldwide - both lawyers and non-lawyers - with basic tools to address the main international legal issues they may encounter both bilaterally and in multilateral negotiations and forums. It features chapter from current or former legal advisers to the ministries of foreign affairs of a representative group of countries alongside the legal advisers of international organizations and institutions with extensive experience in their respective fields. The book offers a practical perspective, without delving into abstract theoretical discussions or issues which, despite being relevant in other contexts, are less so in the diplomatic field.